The Impact of Developing Educational Administration on Improving the Educational and Instructional System - Hosni Soud (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims at identifying the impact of developing educational administration on improving the educational and instructional system in the ministry of education in Jordan. Descriptive approach was adopted, and the study population consisted of schools in irbid governorate in which different apporoaches in curriculum design are applied. The sample of the study consisted of 20 leaders selected using the random sampling method in the first semester of the academic year 2019-2020. A questionnaire consists of 35 items distributed to four categories, namely leadership, organizational aspects preparation and development and educational policies. The results of the study showed that the Educational administration affects the educational and instructional system. The development of educational administration leads to an improvement in the educational and instructional system. Decentralization of administration increases the speed of improving the educational system. There is a rapid acceptance of change in educational administration, which affects the development of the instructional process. The study recommends that schools should continue in developing educational policies and a qualitative strategy in order to achieve their goals. It is also recommended using the democratic leadership approach to achieve advanced levels of positivity in school performance. The study also emphasized the necessity of developing educational management processes, and linking it with decentralization in education. Also the importance of providing schools with all the needed tools and technologies that support educational process